2005
DOI: 10.1038/sj.ijo.0802962
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial working conditions and weight gain among employees

Abstract: OBJECTIVE:To study the associations between psychosocial working conditions and weight gain. DESIGN, SUBJECTS AND MEASUREMENTS: Data from postal questionnaires (response rate 67%) sent to 40-to 60-y-old women (n ¼ 7093) and men (n ¼ 1799) employed by the City of Helsinki in 2000-2002 were analysed. Weight gain during the previous 12 months was the outcome variable in logistic regression analyses. Independent variables included Karasek's job demands and job control, work fatigue, working overtime, work-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
1
42
1
Order By: Relevance
“…With regard to the effort-reward imbalance model, one prospective and one cross-sectional study found full support (56,57), and one cross-sectional investigation found partial support (58). The demand-control model was fully confirmed in four studies (24,57,59,60) and partially confirmed in eight studies (29,31,44,56,58,(61)(62)(63); in ten investigations there was no association between job strain or single-model components and body weight or weight change, respectively (30,32,35,39,45,(64)(65)(66)(67)(68). However, these inconclusive findings on the relationship between work stress and body weight may reflect the failure to take into account the possibility that stress may cause both weight gain and weight loss.…”
Section: Body Weightmentioning
confidence: 74%
“…With regard to the effort-reward imbalance model, one prospective and one cross-sectional study found full support (56,57), and one cross-sectional investigation found partial support (58). The demand-control model was fully confirmed in four studies (24,57,59,60) and partially confirmed in eight studies (29,31,44,56,58,(61)(62)(63); in ten investigations there was no association between job strain or single-model components and body weight or weight change, respectively (30,32,35,39,45,(64)(65)(66)(67)(68). However, these inconclusive findings on the relationship between work stress and body weight may reflect the failure to take into account the possibility that stress may cause both weight gain and weight loss.…”
Section: Body Weightmentioning
confidence: 74%
“…This might explain, in part, the mechanism underpinning the interactive effects proposed by Kivimäki et al (J Occup Health 2010; 52: 66-73) Key words: Body mass index, Hyperphagia, Obesity, Psychological stress When stressed, some people lose and other people gain weight 1) . Although some studies have found associations between stressful work environments and increased body mass index (BMI) [2][3][4][5][6][7] , others have reported no associations between these variables [8][9][10][11][12][13] . Moreover, a highly stressful work environment was associated with low BMIs in several samples 14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in Australia, Hong Kong and Finland have also found that long working hours are associated with an increased risk of obesity (Di Milia and Mummery 2009;Ko et al 2007;Lallukka et al 2005Lallukka et al , 2008aOstry et al 2006). These findings are important in an Australian context given that the proportion of Australian adults working long hours (i.e.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, individuals who work longer hours may also have an increased risk of obesity because of increased consumption of snacks and fast food resulting from an actual, or perceived, lack of time (Lallukka et al 2005(Lallukka et al , 2008aNakamura et al 1998). …”
Section: Introductionmentioning
confidence: 99%